Economic costs of health and social care for a child with a life-limiting condition in their last year of life: a systematic review - Nathan Bray; Jane Noyes; Louise Prendergast; Ellie Crane (BMJ Paediatrics Open)
Aim To systematically review and descriptively synthesise the costs associated with any health and/or social care services provided to children with a life-limiting condition, in their last year of life.Methods Systematic review using MEDLINE, EMBASE, CENTRAL Cochrane Library, CINAHL and other specialist databases to identify articles published between 2004 and 2024. Duplicates were removed and two authors screened the articles and abstracts independently. Full-text articles were assessed for eligibility, with quality assessment conducted using the Drummond checklist. The findings were exported into tables and summarised narratively. Costs from each study were calculated per person per month and inflated to 2024 US dollars.Results 20 records were eligible for final inclusion. Services reported were varied as were approaches to estimating costs. In general, younger children required more intensive and higher cost care. Costs increase in the final months of life, and specialist paediatric palliative care interventions were associated with overall lower costs through reductions in hospital admissions and length of stay.Conclusions It was not possible to present a reliable robust estimate of the economic costs of services and resources due to limited and heterogenic data. Further research is needed to identify the full range of resources, and services associated with caring for children with life-limiting conditions in their last year of life, to support healthcare planning and resource allocation.